FINANCIAL TECHNOLOGY AND THE GROWTH OF THE LISTED DEPOSIT MONEY BANKS IN NIGERIA (Journal of Global Accounting, 2025)
This study examined the impact of financial technology on listed deposit money banks in Nigeria. The study covered the period of 2005 to 2023 and employed Autoregressive Distributed Lag Model (ARDL) to analyses the annual time series data. While the data for financial technology index and return on assets were obtained from World Development Indicators, the data for automated teller machine, mobile money transactions and credit to private sector were sourced from Central Bank of Nigeria statistical Bulletin. The findings reveal that financial technology and automated teller machine have a significant positive impact on deposit money banks’ survival in Nigeria. However, it was observed that mobile banking transactions and credit to private sector have negative and insignificant effects on the survival of deposit money banks in Nigeria. It is recommended that banks should invest heavily in financial technology that would make banking services free of any network hitches that usually cause delay in transactions and double debit of customers account without dispensing cash. If this is done, mobile banking transactions and other forms of payment platform will be fortified.
Keywords: Financial technology; Growth of deposit money bank; Mobile bank